2008
DOI: 10.1038/leu.2008.257
|View full text |Cite
|
Sign up to set email alerts
|

Genome profiling of acute myelomonocytic leukemia: alteration of the MYB locus in MYST3-linked cases

Abstract: The t(8;16)(p11;p13) is a rare translocation involved in de novo and therapy-related myelomonocytic and monocytic acute leukemia. It fuses two genes encoding histone acetyltransferases (HATs), MYST3 located at 8p11 to CREBBP located at 16p13. Variant translocations involve other HAT-encoding genes such as EP300, MYST4, NCOA2 or NCOA3. MYST3-linked acute myeloid leukemias (AMLs) share specific clinical and biological features and a poor prognosis. Because of its rarity, the molecular biology of MYST3-linked AML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Hierarchical clustering and PCA revealed a common signature of the HOX cluster genes overexpressed in both subtypes. This is in line with recent data from Camos et al 51 and Murati et al, 52 who detected overexpression of HOXA9, HOXA10 and their cofactor MEIS1 in their series of t(8;16). We also confirm the overexpression of PRL, CHD3, CPEB2, NR2F6 and RET genes in AML with t(8;16) and decreased expression of the CCND2 and HINT1 genes.…”
Section: Gene Expression Profiling In Aml With T(8;16) T Haferlach Et Alsupporting
confidence: 81%
“…Hierarchical clustering and PCA revealed a common signature of the HOX cluster genes overexpressed in both subtypes. This is in line with recent data from Camos et al 51 and Murati et al, 52 who detected overexpression of HOXA9, HOXA10 and their cofactor MEIS1 in their series of t(8;16). We also confirm the overexpression of PRL, CHD3, CPEB2, NR2F6 and RET genes in AML with t(8;16) and decreased expression of the CCND2 and HINT1 genes.…”
Section: Gene Expression Profiling In Aml With T(8;16) T Haferlach Et Alsupporting
confidence: 81%
“…The identification of submegabase-sized CNAs (that contain Յ3 genes; Table 1) will allow us to prioritize the study of genes that are likely to contribute to AML pathogenesis. For example, the MYB oncogene was altered in 2 very small CNAs, which may represent a cryptic chromosomal translocation or duplication, as previously described in T-ALL (25)(26)(27). Finally, arraybased studies can sometimes detect copy number changes not identified by cytogenetics despite being of adequate size (Ͼ5 Mb), presumably owing to technical failures during the expansion of cells for cytogenetic analysis or loss of a clone with a cytogenetic abnormality during in vitro propagation.…”
Section: Discussionmentioning
confidence: 90%
“…This can be caused by translocation, leading to deregulation of the MYB gene, as in childhood T-cell acute lymphoblastic leukemia (Clappier et al, 2007), or stabilization of MYB mRNA, as in adenoid cystic carcinomas of the breast, head and neck (Persson et al, 2009). Local duplication of MYB has also been reported with another subgroup of T-cell acute lymphoblastic leukemia (Clappier et al, 2007;Lahortiga et al, 2007) and in a subgroup of acute myelomonocytic leukemia (Murati et al, 2009). Thus, deregulation of c-Myb expression is associated with oncogenicity.…”
mentioning
confidence: 99%